Electrochemical and photochemical characterization of novel ferrocenyl–azobenzene labeled PNA monomers for DNA detection - Li, Jindu; Chen, Miao; Zhang, Haobo; Liu, Sheng (Inorganic chemistry communications, 2008)
Ferrocenyl–azobenzene carboxylic acid labeled thymine PNA (Fc–Azo–T) monomer was synthesized and showed highly electrochemical and photochemical activity. The influence of isomerization to electrochemical properties was discussed. Ferrocenyl–azobenzene carboxylic acid was synthesized and used as electrochemically and spectroscopically active marker that was conjugated to thymine PNA monomer. Ferrocenyl–azobenzene labeled PNA monomer of thymine (Fc–Azo–T) shows highly electrochemical and photochemical activity. The detection limit of Fc–Azo–T can reach 10−6M by using differential pulsed voltammogram (DPV), and the UV–vis limit is in the order 10−7M in ethanol. Fc–Azo–T can undergo facile isomerization by photoirradiation. The results give great motivity for synthesizing ferrocenyl–azobenzene labeled PNA oligomers used as an effective electrochemical and photochemical probes.